2018
DOI: 10.1111/ddg.13431
|View full text |Cite
|
Sign up to set email alerts
|

The status of dermoscopy in Germany – results of the cross‐sectional Pan‐Euro‐Dermoscopy Study

Abstract: The findings presented herein ought to be integrated into future residency and continuing medical education programs with the challenge to improve dermato-oncological care and to expand the diagnostic spectrum of dermoscopy to include inflammatory skin diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
11

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 37 publications
1
14
0
11
Order By: Relevance
“…Dermoscopy is a helpful tool for the differentiation of benign nevi and cutaneous melanomas [1][2][3][4]. As shown in previous meta-analyses, dermoscopy markedly improves the sensitivity and specificity of melanoma diagnosis in comparison to examination with the unaided eye [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Dermoscopy is a helpful tool for the differentiation of benign nevi and cutaneous melanomas [1][2][3][4]. As shown in previous meta-analyses, dermoscopy markedly improves the sensitivity and specificity of melanoma diagnosis in comparison to examination with the unaided eye [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosequiz Abbildung 2 Die Dermatoskopie zeigte eine zentrale blutige Kruste und eine rosa-weiße Peripherie mit atypischen haarnadelförmigen und linearen Gefäßen. [3,4].…”
Section: English Online Version On Wiley Online Libraryunclassified
“…A meta‐analysis of 104 study publications found dermoscopy increases sensitivity over the naked‐eye examination from 76% to 92% at a fixed specificity of 80% (Dinnes, Deeks, Chuchu, et al, 2018). However, appropriate training is crucial: user expertise and training in dermoscopy improves diagnostic accuracy (Dinnes, Deeks, Chuchu, et al, 2018), and lack of training is a barrier to use among dermatologists (Blum et al., 2018). Furthermore, with appropriate training, dermoscopy use by primary care physicians has been associated with increased diagnostic accuracy and fewer unnecessary excisions and referrals (Jones et al., 2019).…”
Section: Dermoscopymentioning
confidence: 99%